THE INFLUENCE OF INNOVATION CAPABILITY AND HUMAN CAPITAL TO THE BUSINESS PERFORMANCE OF LEILEM FURNITURE SME’S UNITS - Yosua Giovani Walukow; Willem J. F. A. Tumbuan; Emilia M. Gunawan (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2023)
Business Performance is one important characteristic that really exhibit the toughness from all business players in the market, especially from business units under SMEs system. Innovation Capability and Human Capital are two essential factors for establishing, maintaining and increasing Business Performance from any company or business unit. This study aims to figure out the influence of Innovation Capability and Human Capital toward the Business Performance of Leilem Furniture SME’s Units. Overall population in this research is Leilem Furniture SME’s Units City and the chosen sample is 30 respondents. Data analysis uses multiple linear regressions analysis method. This research result proves that Innovation Capability and Human Capital simultaneously and partially influence the Business Performance of Leilem Furniture SME’s Units. Owners and management from each one Leilem Furniture SME’s Units have to preserve and boost Innovation Capability and Human Capital in every business unit and deliberate other factors that influence the Business Performance of Leilem Furniture SME’s Units.   Keywords: innovation capability, human capital, business performance